Improved technologies for reducing post-harvest losses - Mutungi, Christopher; Abass, A.; Fischer, Gundula; Kotu, Bekele Hundie (CAB International, 2022)
This chapter outlines several post-harvest loss reduction technologies validated by the Africa RISING program that will improve the efficacy of drying, threshing, and storage operations, and gives evidence of their potential impact. The chapter also provides evidence on the cumulative benefits of combining all three technologies.